Taking the Green Road Towards Pharmaceutical Manufacturing - Federsel, Hans-Jürgen (Synthesis, 2022)
The introduction of the Green Chemistry Principles in the late 1990s formed the basis for a transition to a greener environment. These Principles have become an integral part in the work on designing chemical processes, especially for large-scale manufacture. The ultimate target is the achievement of a sustainable production method allowing hundreds of tons of valuable materials to be prepared. For this purpose, a holistic view must be applied to the elements constituting a fully-fledged process encompassing layout of the synthetic route, defining starting materials and their origin, output of product and quality features, quantity of effluent streams and waste, recovery and recycling of chemicals involved, and energy consumption. These parameters form a complex matrix where the individual components are in a complicated relationship with each other. This short review addresses these issues and the benefits of life-cycle assessment and metrics commonly used to measure the performance of chemical manufacturing – all from a pharmaceutical industry perspective as experienced by the author.1 Introduction: Facing Severe Challenges2 The Historical Context: Addressing an Image Problem3 Prospects, Drivers and Roadmap for the Green Future4 Living by the Principles: Industrial Perspectives5 Taking the Green Route – Catalysis Leading the Way: Case Stories6 State of the Art: How Green Are We?7 Sending Signals, Creating Impressions: Focus on Communication8 Conclusions
Keywords: green chemistry; sustainability; pharmaceutical manufacturing; catalysis; process design; E factor; PMI